DOI: 10.31274/rtd-180813-15214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of carbohydrates for baby pigs

Abstract: The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleed-through, substandard margins, and improper alignment can adversely affect reproduction. In the unlikely event that the author did not send a complete manuscript and there are missing pages, these will be noted. Also, if unauthorized copyright material had to be removed, a note will indicate the deletion. UMI UMI Microform DP13291

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 2 publications
4
12
0
Order By: Relevance
“…These results are in harmony with those of Hudman (1956) who showed that lactose was the carbohydrate of choice for the baby pig when a coin-soy diet was used. No attempt was made in this experiment to maintain an iso-caloric diet because the productive energy value of 6l6 calories per pound for whey did not seem realistic when compared to 1334-calories per pound for sucrose.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…These results are in harmony with those of Hudman (1956) who showed that lactose was the carbohydrate of choice for the baby pig when a coin-soy diet was used. No attempt was made in this experiment to maintain an iso-caloric diet because the productive energy value of 6l6 calories per pound for whey did not seem realistic when compared to 1334-calories per pound for sucrose.…”
Section: Resultssupporting
confidence: 89%
“…This supports the woik of Hudman (1956) who demon strated that lactose was the carbohydrate of choice when soy bean oilmeal was the protein source.…”
Section: Direct Comparison Studiessupporting
confidence: 79%
See 2 more Smart Citations
“…ACTOSE and sucrose were reported by Hudman (1956) to be preferred carbohydrates for pig starter rations. Lactose gave the best growth response when fed with soybean oil meal; sucrose with milk protein.…”
mentioning
confidence: 99%